FEATURES OF FORMATION AND REGENERATION OF NATURAL OAK FOREST STANDS OF THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Rumiantsev, M. G.; Solodovnik, V. A.; Chygrynets, V. P.; Lunachevskiy, L. S.; Kobets, O. V. (Forestry and Forest Melioration, 2018)
Introduction Natural oak forest stands of Left-bank Forest-Steppe perform important ecological, recreational, soil-protective, water-conservation functions and are the unique centers of conservation of biological and genetic diversity. Clearcutting is the most common method used in plain forests of Ukraine after which forest plantations are created on felled areas. This results in the loss of biological diversity, activates the weakening processes and reduces a potential self-regeneration capacity. The aim of the research was to study the current state and characteristics of the formation and regeneration of natural oak forests in Left-bank Forest-Steppe of Ukraine. Materials and Methods The study was conducted in natural oak forest stands of different age, composition and site class in the conditions of fresh maple-lime fertile oak forest type in State Enterprise “Krasnopilske Forest Economy”. The typological analysis methods were applied for the assessment of forest site capacity ratio. The natural regeneration accounting was made using the technique developed in URIFFM. The advance growth was distributed by species, groups of height, age and state of vitality. Results Forest stands of the enterprise are represented by 31 tree species, among which there are shrubs. English oak (Quercus robur L.) stands are prevailing by area; their share is 63.1% of the total area covered with forest vegetation. The artificial oak stands grow on an area of 6,369.2 ha, and natural ones on an area of 7,113.3 ha. The age-related structure of natural oak stands is unbalanced. Predominant are middle-aged stands and stands of approaching maturity. The value of the forest site capacity ratio in the fresh maple-lime fertile oak forest type varies between 70 and 80 %. Weighted average is 79 %. Analysis of the oak trees distribution on permanent sample plots by health status categories indicates a decrease in the share of trees of 1 and 2 categories (healthy and weakened ones) with aging in mixed oak stands. In the conditions of fresh maple-lime oak forest the total amount of regeneration under the canopy of oak stands is ranging from 10.00 to 35.72 thousand pcs?ha-1. There are 6 tree species in the composition of advance growth. Conclusions Targeting on natural regeneration of oak stands it is necessary to use effectively the natural renewal of economic-valuable species, especially oak and ash. It will provide maintenance of genetic variety of the natural mixed oak biocenosis. Scientifically-based measures are developed to optimize the formation and regeneration of natural oak forest stands in SE “Krasnopilske Forestry”.